MENGENAL SISTEM GNOTOBIOTIK DAN PERANANNYA PADA BUDIDAYA BIOTA LAUT - Marenda Pandu Rizqi (OSEANA, 2018)
INTRODUCTION TO GNOTOBIOTICS AND ITS ROLE IN MARICULTURE. Initial colonization of microbial community in marine larvae is one of the important stage in larval development in terms of subsequent growth, immunostimulation, and pathogen elimination. Gearing towards environmentally sustainable manner of aquaculture, early microbial manipulation in larval stage may provide an alternative in efficient and productive larviculture. One of the tool to further study the host-microbe interaction is through in-vivo culture of axenic and gnotobiotic larvae, in which a germ-free larvae was produced, and subsequently induced with single strain benign microbe to observe its response and characteristics. Several methods and protocols to obtain axenic-gnotobiotic condition is highlighted, along with the current development of gnotobiotic research, particularly in commercially valuable saltwater fish, e.g. Atlantic cod and European seabass. The development of novel gnotobiotic protocols combined with different scientific approach, e.g. gene expression, quorum sensing, immunostimulants, and purified diets may provide better insight in host-microbe interaction of marine biota, which in turn will benefit the implementation of specific probiotics, prebiotics, diets, and microbial regulation in marine larviculture.